KERENTANAN TIGA JENIS ROTAN KOMERSIL TERHADAP SERANGAN JAMUR - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1989)
The  result  of  a  study   on  the  susceptibility    of  rattan  to  fungal  attack.   Three  rattan  species  i.e.   irit (Calamus  trachy- coleus  Becc.),   manau  (C.  manan  Miq.)  and  semambu   (C. scipionum Lour.)   both peeled  and  unpeeled  were kept  out  door. Fungal  infestation   was than  observed  after  one,  two,   four  and  eight  week  periods.  At  the end of experiment,   each rattan sample  was split  into  two  halves to observe  internal  discoloration.   The result showes  that  irit was most  susceptible   to stain attack   and  infestation   on peeled  cane seems  to  be more  severe  compared   with  unpeeled  ones.  The  average rate of  infes- tation  of  the  rattan  species  studied was  10.59   % (4.65  -   14,92  %) per  week.   The  lowest  and  highest  rate of  infestation were shown  respectively   by  unpeeled  manau and peeled  irit rattan.  It was also revealed  that  93.33  % of  the  test speciments were  internally  stained,   of  which  46.67  % were badly stained.  Semambu  rattan seems  to  beresistant  to fungal  infestation, most  of  which showing  low degree  of  internal stain.